A century of foreign investment in the Third World - Twomey, Michael J. (Routledge studies in international business and the world economy, 2000)
Annotation The late twentieth century has witnessed a dramatic upsurge in foreign direct investment in the Third World. Based upon thorough statistical analysis, the book presents exhaustive case-studies of foreign investment policy in 'metropolitan' countries and of the experiences of 'host' countries throughout Africa, Asia and Latin America. With a wide geographical and historical focus, it also makes an important contribution to current debates on dependency theory.